Management of Islamic Learning Programs in Improving The Quality of Educations in Thailand - Permana, Hinggil; Wahyudin, Undang Ruslan; Bidohbudee, Miss Saina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
The study aims to analyze the Islamic learning management model of Islamic boarding schools in Thailand through planning, organizing, implementing and evaluating. The method used in this study is qualitative. Data collection is carried out by observation, interview and documentation techniques. The data analysis technique is carried out through data reduction, data display, data interpretation, and finally, making conclusions. The results of research on the management of Darul Barakah cottage show that cottage management is already running, with the central manager being the leader of the ustadz. However, in implementation, it is assisted by the administrators in their respective portions, duties and responsibilities. Thus Darul Barakah lodge has done an excellent managerial even though it could be better. With a strong desire and enthusiasm to advance the education system, the learning management of Pondok Darul Barakah can change from the original Salafi form can be reconstructed to modern learning. The implication is that the learning management system of Islamic boarding schools in Thailand is the same as in Indonesia because they adopt the existing Islamic boarding school education system in Indonesia, starting from the admission of students and the learning system to graduation.